2022
DOI: 10.1111/ajco.13877
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical predictors of tumor response after neoadjuvant therapy in rectal cancer

Abstract: Background Patients who have a good clinical and/or pathologic response to neoadjuvant chemoradiotherapy (nCRT) for rectal cancer have better long‐term outcomes and can potentially be spared morbid surgery. This study aimed to identify pretreatment clinical and biochemical predictors of response to neoadjuvant treatment for rectal cancer. Methods Patients undergoing neoadjuvant therapy for rectal cancer between 2007 and 2022 were retrospectively included. Those patients who achieved a complete clinical respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Domestic studies also suggested that TNT did not significantly improve the survival prognosis of rectal cancer patients. A subgroup analysis of several studies showed that the OS and DFS of pCR patients were much better than those of nonpCR patients[ 43 , 44 ]. This suggests that the survival prognosis of rectal cancer patients may be linked to local tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic studies also suggested that TNT did not significantly improve the survival prognosis of rectal cancer patients. A subgroup analysis of several studies showed that the OS and DFS of pCR patients were much better than those of nonpCR patients[ 43 , 44 ]. This suggests that the survival prognosis of rectal cancer patients may be linked to local tumor control.…”
Section: Discussionmentioning
confidence: 99%